Drug metabolising enzyme polymorphisms and chemotherapy-related ovarian failure in young breast cancer survivors. (3rd April 2021) - Charo, Lindsey M.; Homer, Michael V.; Natarajan, Loki; Haunschild, Carolyn; Chung, Karine; Mao, Jun J.; DeMichele, Angela M.; Su, H. Irene
Abstract: Cyclophosphamide is associated with chemotherapy-related ovarian failure (CROF) in breast cancer survivors, however little is known about predicting individual risks. We sought to identify genetic alleles as biomarkers for risk of CROF after cyclophosphamide treatment. One hundred fifteen premenopausal women with newly diagnosed breast cancer were genotyped for single nucleotide polymorphisms (SNPs) in genes involved in cyclophosphamide activation ( CYP3A4 and CYP2C19) and detoxification ( GSTP1 and GSTA1 ). Patients prospectively completed menstrual diaries. With median follow up of 808 days, 28% experienced CROF. Survivors homozygous for the GSTA1 minor allele had lower hazards for developing CROF (HR 0.22 [95% CI 0.05–0.94], p =.04), while survivors homozygous for the CYP2C19 minor allele had higher hazards for developing CROF (HR 4.5 [95% CI 1.5–13.4], p =.007) compared to patients with at least one major allele. In separate multivariable models adjusting for age and tamoxifen use, the associations were no longer statistically significant ( GSTA1 HR 0.24 [95% CI 0.06–1.0], p =.05; CYP2C19 HR 2.5 [0.8–7.6], p =.11). CYP3A4 and GSTP1 SNPs were not significantly related to CROF. In younger breast cancer survivors undergoing cyclophosphamide-based chemotherapy, genetic variation in CYP2C19 and GSTA1 merits further study to determine its relationship with CROF. IMPACT STATEMENT: What is already known on this subject? Young breast cancer survivors face important potential implications of chemotherapy-related ovarian failure (CROF). Little is known about individual risk for CROF. Cyclophosphamide, a particularly gonadotoxic drug commonly used in breast cancer treatment, is metabolised by various cytochrome p450 enzymes. Studies have shown genetic variation in p450 enzymes is associated with differential clinical outcomes after cyclophosphamide treatment: breast cancer patients homozygous for GSTA1 minor allele had improved overall survival; lupus patients homozygous for CYP2C19 minor allele had increased risk for CROF; and CYP3A4*1B I was associated with decreased risk for CROF. What do the results of this study add? We show a surprising opposite trend for the risk of CROF in breast cancer patients with GSTA1 and CYP2C19 variants, while we did not show a significant risk for genetic variation in CYP3A4 (which had previously been shown to have a protective effect) or GSTP1 . What are the implications of these findings for clinical practice and/or further research? This study shows the complexity of genetic variation in predicting outcomes to treatment. We advocate for future replicative studies to potentially validate GSTA1 and CYP2C19 and definitively negate CYP3A4 and GSTP1 as biomarkers for risk of CROF after cyclophosphamide treatment. Understanding genetic variation in chemotherapy metabolism has the potential to individualise treatment regimens to maximise efficacy and minimise toxicity.